Implementasi Model One Stop Service di PLHUT: Tinjauan Kebijakan dan Dampaknya terhadap Kepuasan Jemaah Haji - Zainar Inayah (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy document discusses efforts to improve "One Stop Service" for Hajj pilgrims at the Integrated Hajj and Umrah Service Centers (PLHUT). The main problem identified is the inconsistent implementation of Standard Operating Procedures (SOPs) across the PLHUTs. This inconsistency stems from several factors, including: (1) low digital literacy among pilgrims, particularly the elderly, which hinders service effectiveness despite the existence of digital systems; (2) limited human resources, budget, modules, time, and manasik guidance facilities; and (3) the complexity of service flows and multi-agency bureaucracy involving many parties (such as the Ministry of Religious Affairs and banks). Furthermore, the absence of regulations requiring banks receiving deposits to occupy PLHUT buildings also hinders the implementation of "One Stop Service." This document uses an Urgency, Seriousness, Growth (USG) analysis and finds that inconsistent SOP implementation is the most fundamental problem that needs to be prioritized. The root of the problem is identified as a hierarchical and non-service-focused organizational design, as well as the complexity of the multi-agency bureaucracy. Based on an analysis of bureaucratic theory, open systems, and collaboration, and supported by laws and regulations, this document offers several policy alternatives. Based on William N. Dunn's criteria analysis, the most recommended alternative is to formulate Technical Guidelines/Instructions for the Implementation of Integrated Digital Services (Single Window Hajj-Umrah). This recommendation aims to create effective, transparent, and responsive services through an integrated digital system, which is expected to address SOP inconsistencies, integrate data across agencies, and improve overall service quality.